CLINICAL SIGNIFICANCE OF MEDICINAL PREPARATIONS REDUCING OXIDATIVE STRESS IN THE HUMAN BODY - O`ktamova N.B; Boymuratov F.T (ILMIY YANGILIKLAR VA INTELLEKTUAL TADQIQOTLAR, 2025)
Abstract: Oxidative stress, caused by an imbalance between the production of reactive oxygen species (ROS) and the antioxidant defense system, plays a key role in the development of numerous chronic and degenerative diseases. The regulation of oxidative processes through pharmacological and natural antioxidant preparations has become a central focus of modern biomedical research. Medicinal substances that reduce oxidative stress, including vitamins (C, E), polyphenols, flavonoids, and enzymatic antioxidants such as superoxide dismutase, have demonstrated significant clinical benefits in preventing cellular damage, inflammation, and premature aging. Clinical studies show that targeted antioxidant therapy can improve cardiovascular health, enhance immune function, and support neurological stability. The clinical significance of these agents lies in their potential to maintain redox homeostasis and prevent disease progression when used appropriately and under medical supervision.